ANALISIS PENGARUH KOMPETENSI INDIVIDU, DISIPLIN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. READS MEDIA INDONESIA - Nursahdi Saleh (Jurnal Publikasi Manajemen Informatika, 2025)
This study aims to explore, analyze, and interpret the impact of Individual Competence, Work Discipline, and Work Motivation on the performance of employees at PT. Reads Media Indonesia. The research approach used is descriptive quantitative, with a population and sample consisting of 36 employees. Data collection was conducted through interviews, questionnaires, and literature studies. The data obtained will be analyzed using statistical tools and SPSS version 24 software. The research results show that: 1. Individual Competence has a positive and significant impact on the performance of employees at PT. Reads Media Indonesia. In general, Individual Competence has a strong influence on improving employee performance, which is a crucial factor in achieving organizational goals. 2. Work Discipline also has a positive and significant impact on the performance of employees at PT. Reads Media Indonesia. Competence is an important factor that supports employees in optimally developing their potential to support organizational goals with full awareness. 3. Work Motivation also has a positive and significant impact on performance at PT. Reads Media Indonesia. The main factors in the work environment include the atmosphere and supporting facilities that play an important role in the execution of work tasks.